Evacuation of Persons from Selected Departments in High-Rise Buildings of Healthcare Facilities - Silvie Benesova; Isabela Bradacova; Thomas Jager (Communications - Scientific letters of the University of Zilina, 2016)
The article deals with the evacuation of persons from hospital bed wards in high-rise buildings of medical facilities. It presents a proposal for a systems approach and provides a subsequent supportive methodology and tools for planning and implementation of the evacuation of persons with disabilities, which is based on data collection and analysis.